Design of Mobile and Robotic Observing System with Special Telescope Baffle for Searching Young Lunar Crescent - Dhani Herdiwijaya; Mitra Djamal; Hendra Gunawan (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2012)
The visibility of very young lunar crescent near the Sun at western horizon after sunset are indispensable important factor in determining important religious Islamic calendar. One can see it at horizon after the sunset as this is the less stringent condition However, in an advanced scientific and technological based, the observation of lunar crescent near the Sun can be undertaken in broad daylight before sunset. The research project will study and develop some additional observing tools, image acquisition and image processing procedures for mobile and robotic observing system that one enable to search the very young crescent in broad daylight. The main problem is how to minimize the atmospheric and instrumental stray light that can obscure the information from the very young crescent image from the daylight background. We have developed and tested a simple extended telescope baffle that can reduce the incoming stray light from the sky and environment. Hence, it will increase the contrast of the lunar crescent. Some requirements and optimization have been applied for the robotic observing system (telescope and its mounting), image acquisition and image processing procedures. The free software and digital camera are used. The observational main constraint was the cloudy sky on the first day of lunar calendar. The progresses will be reported